Manufacturing of Ceramic Reinforced Metal Matrix Composites (Al/Sicp) And Their Characterization Through Powder Metallurgy Methods - Jepriandi Ginting (Lembaga Layanan Pendidikan Tinggi Wilayah I Sumatra Utara (LLDikti I), 2022)
Metal Matrix Composites is two or more combination material with aluminum metal as matrix and devolved to fix metal act, strength, high temperature stability and hardness. Metal matrix composites have been developed so many because it has low density, corrosion proof, cheap and easy fabrication. Powder metallurgy technique is one of metal matrix composites fabrication process in solid state that is still developed because more economic, doesn't need difficult equipment. Aluminum that use in this research is Al alloy type 2124. Metal matrix composites fabrication process with powder metallurgy method using wet mixing with pure ethanol, cold compaction 300 MPa and inert gas atmospheric using Nitrogen gas (N2) at sintering process. Variation of sinter temperature that used is 450, 500, 550, and 600 oC with highly temperature average 5 oC/min and holding time for 1 hour and with speed flow Nitrogen gas (N2) 5 lt/min with pressure 1000 kgf/cm2. From research result can be concluded the mechanical properties and physical properties from metal matrix composites reinforced ceramics Al/SiCp increase with sinter temperature highly and with reinforcement particle addition SiC can increase mechanical properties and physical properties such as: hardness, wear resistance, coefficient of thermal expansion and corrosion resistance. From microstructure analysis, particle Sic distributed homogeneously at test specimen based on SEM analysis, and structure crystal analysis test result XRD show that dominant phase appear is Al, and Sic.